Designing an integrated Halal value chain model for sustainable fisheries: A case study from northern coastal of Java, Indonesia - Takhim, Muhamad; Ayuningtyas, Rosida Dwi; Fatchurrohman, M; Az Zahro , Firial Annasa (Journal of Islamic Economics Lariba, 2025)
IntroductionThe concept of the halal value chain has been widely applied in the food, logistics, and pharmaceutical sectors to ensure the halalness of products from upstream to downstream. However, the fisheries sector, particularly in the northern coastal region of Java, lacks an integrated halal value chain model that incorporates sustainability principles.ObjectivesThis research aims to design a contextual halal value chain model that combines halal and sustainability aspects at each stage of the fisheries value chain.MethodA case study-based qualitative approach is used with secondary data analysis from various official and academic sources. The analysis is conducted through content analysis, thematic synthesis, and mapping of halal critical points across five main stages: production, collection, processing, distribution, and consumption.ResultsThe findings indicate that business actors do not fully comprehend halal standards, lack effective halal logistics, and have a weak certification and supervision system. ImplicationsThe proposed model emphasizes the importance of halal control, the integration of economic, social, environmental, and health sustainability, and the active participation of local communities. This model is expected to increase the added value of fishery products, expand access to the global halal market, and strengthen the sustainability of the coastal fisheries sector.Originality/NoveltyThis research contributes to the development of the halal value chain theory in the context of the fisheries industry, providing applicable policy implications for strengthening the national halal economy.